Periodontal implication of bonded and removable retainers: A comparative study (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
The purpose of this study is to compare the periodontal health of the lower anterior teeth retained with the use of removable and fixed retainers. Fifty four cases receiving comprehensive orthodontic treatment in between 10 to 30 years were randomly selected and divided into 2 groups of 27 each. One group was given removable retainers and other was given fixed retainers. The periodontal status of the patients was accessed with bleeding on probing index, Plaque index and Calculus index. The mean plaque index in case of removable retainers at 1st, 3rd and 6th month were 0.5, 1.0 and 1.7 where as in case of fixed retainers that were 1.8, 3.0 and 4.5. The mean dental calculus index in case of removable retainers at 1st, 3rd and 6th month were 0.0, 0.1 and 0.1 where as in case of fixed retainers that were 0.1, 0.9 and 1.8. In conclusion, removable retainers are superior in oral hygiene maintenance, yet the use of fixed retainers cannot be denied.